A high-nickel positive electrode material, a preparation method thereof, a positive electrode sheet, and a lithium ion battery

CN123017949APending Publication Date: 2026-10-30TIANJIN GUOAN MGL NEW MATERIALS TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611486333.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-23
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

但是该复合层的组成复杂,难以保证大批量生产中的一致性

Benefits of technology

[0054](1)本申请通过在高镍正极材料的基体内部构建由核心至表面指数减小的三维贯通孔隙结构,并在基体表面构建超薄玻璃态锂硼磷氧化物包覆层与之协同,在保持压实密度≥3.5g/cm3的同时,实现了≥240mAh/g的高放电比容量,以及100周保持率≥95%的长循环寿命,且循环产气量下降65%以上,实现了高安全性,解决了高镍正极材料倍率性能与能量密度、循环性能和安全性能间相互制约的难题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123017949A_ABST
    Figure CN123017949A_ABST
Patent Text Reader

Abstract

The application relates to a high-nickel positive electrode material and a preparation method thereof, a positive electrode sheet and a lithium ion battery. The high-nickel positive electrode material comprises a base body and a coating layer. The average porosity of the base body within a range of 0-1 / 20R from the core is phi0, the porosity within a range of 1 / 20R to R from the core is exponentially distributed, and satisfies phi(r)=phi0*exp(-r / R) ‑kr , r is normalized by the radius R of the base body; and the material of the coating layer comprises glassy lithium boron phosphorus oxide. According to the application, a three-dimensional through-pore structure with an exponential decrease from the core to the surface is constructed in the base body of the high-nickel positive electrode material, and an ultrathin glassy lithium boron phosphorus oxide coating layer is constructed in cooperation, so that the high-nickel positive electrode material has high tap density and compaction density, the ion transmission capacity and structural stability of the high-nickel positive electrode material are effectively improved, the base body is protected from electrolyte corrosion, the byproduct gas is reduced, and the rate performance and cycle performance are simultaneously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion battery technology, specifically to high-nickel cathode materials, and more particularly to a high-nickel cathode material and its preparation method, cathode sheet, and lithium-ion battery. Background Technology

[0002] High-nickel cathode materials have become a hot topic in the research and application of lithium-ion battery cathode materials due to their advantages of high charge-discharge voltage, high charge-discharge specific capacity, and high energy density. However, in practical applications, as the proportion of Ni in transition metal elements continues to increase, the number of lithium-ion insertions and extractions increases, and the volume change of high-nickel cathode materials is drastic, leading to easy particle cracking, poor cycle performance, and the high nickel content makes the surface chemical properties of the material active, which can easily cause side reactions with the electrolyte to generate gas, leading to safety hazards. In addition, in order to increase the compaction density, the disordered porosity inside the high-nickel cathode material decreases, making it difficult to achieve capacity and significantly deteriorating rate performance. It is difficult to achieve high capacity, rate performance and high compaction density in a coordinated manner.

[0003] CN112194200A discloses a method for preparing a high-nickel cathode material with low residual alkali, high compaction, and uniform coating. The method includes first obtaining a large-particle high-nickel polycrystalline primary sinter using a large-particle high-nickel polycrystalline precursor, then obtaining a small-particle high-nickel polycrystalline primary sinter using a small-particle high-nickel polycrystalline precursor. The large and small-particle high-nickel polycrystalline primary sinters are then wet-mixed with lithium hydroxide and a soluble salt, and finally mixed uniformly with a coating agent before calcination to obtain the high-nickel cathode material. This invention utilizes the mixing of large and small particles to reduce the gaps between particles and achieve a higher compaction density; however, this invention does not adjust the porosity of the high-nickel cathode material particles themselves.

[0004] CN121839601A discloses a high-nickel cathode material and its preparation method. The matrix material adopts a high-nickel chemical system and introduces multiple specific elements for doping. While ensuring the material has a high discharge specific capacity advantage, the stability of the bulk lattice structure is enhanced by multi-element doping. Furthermore, combined with a double-layer coating structure, the rate performance, long cycle life, and thermal stability are synergistically improved while maintaining the high energy density of the high-nickel material. However, the double coating layer provided by this invention is extremely thin, making it difficult to guarantee the integrity of the coating.

[0005] CN117361645A discloses a high-temperature single-crystal high-nickel cathode material, its preparation method, and its application. The modified single-crystal high-nickel cathode material is coated with a porphyrin-based microporous polymer / polyurethane-calcium carbonate (PACMP / PU-CaCO3) composite layer. The porphyrin-based microporous polymer effectively absorbs CO2 generated by residual alkali on the surface of the cathode material under high temperature and long cycling conditions. The polyurethane-calcium carbonate layer continuously adsorbs byproducts of electrolyte decomposition and releases substances containing LiPO2F2 and Ca. 2+ The active material effectively reduces interfacial side reactions between the electrolyte and the positive electrode, inhibits the growth of lithium dendrites and the generation of alkane gas, and improves the cycle life of batteries made from positive electrode materials. However, the composition of this composite layer is complex, making it difficult to ensure consistency in mass production.

[0006] Therefore, it is of great significance to provide a high-nickel cathode material and its preparation method that can synergistically solve the problems of bulk structure and interface stability. Summary of the Invention

[0007] To address the shortcomings of existing technologies, the present invention aims to provide a high-nickel cathode material, its preparation method, cathode sheet, and lithium-ion battery. This application constructs a three-dimensional interconnected porous structure with an exponentially decreasing core-to-surface ratio within the high-nickel cathode material matrix, and synergistically constructs an ultra-thin glassy lithium boron phosphorus oxide coating layer on the matrix surface. This ensures the high-nickel cathode material possesses high tap density and compaction density while effectively improving its ion transport capability and structural stability, protecting the matrix from electrolyte corrosion, reducing side reaction gas generation, and achieving simultaneous improvement in rate performance and cycle performance.

[0008] To achieve this objective, the present invention adopts the following technical solution:

[0009] In a first aspect, the present invention provides a high-nickel cathode material, the high-nickel cathode material comprising a substrate and a coating layer; the chemical formula of the substrate includes LiNi. x Co y M z O2, where M includes Mn and / or Al, x ≥ 0.6, 0 ≤ y ≤ 0.4, z = 1 - xy; the average porosity of the matrix in the range of 0 to 1 / 20R from the core is φ0, and the porosity in the range of 1 / 20R to R from the core follows an exponential gradient distribution, satisfying: φ(r) = φ0 × e -kr r is obtained by normalizing the radius R of the substrate, 1 / 20 < r ≤ 1, 1.5 ≤ k ≤ 3.0; the material of the coating layer includes glassy lithium boron phosphorus oxide.

[0010] This application identifies the comprehensive influence of internal porosity of high-nickel cathode material particles on rate performance and compaction density, and constructs a three-dimensional through-pore structure within the high-nickel cathode material matrix, with the porosity decreasing exponentially from the core to the surface: the average porosity of the crystal nuclei within the range of 0 to 1 / 20R from the core is φ0, and as the crystal nuclei continue to grow, the porosity follows the formula φ(r) = φ0 × e. -kr The transition is continuous, where r is obtained by normalizing the radius R of the matrix, 1 / 20 < r ≤ 1, and k is the attenuation constant, which uniquely determines the gradient steepness of the pore formation. The larger the value of k, the faster the pores attenuate from the inside to the outside, and the stronger the contrast between "sparse inside and dense outside".

[0011] This application effectively avoids stress concentration by selecting the k value to control the steepness of porosity change. The internal loose region provides a fast ion transport channel and effectively buffers volumetric strain, while the external dense region effectively maintains high tap density, giving the particles high compressive strength. At the same time, it provides an ideal substrate for the uniform construction of ultrathin glassy lithium boron phosphorus oxide coating. The uniform and dense glassy lithium boron phosphorus oxide coating has high lithium-ion conductivity and can protect the porous structure from electrolyte corrosion and effectively suppress side reaction gas production.

[0012] This application designs the internal pore structure of the high-nickel cathode material matrix and constructs an ultra-thin glassy lithium boron phosphorus oxide coating layer on the matrix surface to work synergistically with it. This ensures that the high-nickel cathode material has high tap density and compaction density, while effectively improving the ion transport capacity and structural stability of the high-nickel cathode material, protecting the matrix from electrolyte corrosion, reducing side reaction gas production, and achieving simultaneous improvement in rate performance and cycle performance.

[0013] The pore structure design strategy provided in this application is of great significance for improving the performance of high-nickel cathode materials, especially for ultra-high-nickel cathode materials in which Ni accounts for more than 90 mol% of the transition elements.

[0014] In some embodiments of this application, the average porosity of the matrix in the range of 0 to 1 / 20R from the core is 40% to 50%, and the average porosity in the range of 19 / 20R to R from the core is 1% to 10%.

[0015] In some embodiments of this application, the average porosity of the matrix is ​​15% to 25%.

[0016] In some embodiments of this application, the thickness of the coating layer is 2nm~20nm.

[0017] In some embodiments of this application, the molar ratio of B, P and Li in the glassy lithium boron phosphorus oxide is 1:(0.05~0.2):(0.8~1.2).

[0018] In some embodiments of this application, the tap density of the high-nickel cathode material is 2.3 g / cm³. 3 above.

[0019] In some embodiments of this application, the D50 particle size of the high-nickel cathode material is 8μm~15μm.

[0020] Secondly, this application provides a method for preparing a high-nickel cathode material as described in the first aspect, the method comprising:

[0021] (1) A mixed metal salt solution of Ni salt, Co salt and M salt, a precipitant solution, a complexing agent solution and a template agent solution are introduced into the reactor in parallel to coprecipitate the precursor to obtain a templated precursor.

[0022] During the co-precipitation process, the flow rates of the mixed metal salt solution, precipitant solution, and complexing agent solution are kept constant, while the flow rate of the template agent solution is determined according to V(t) = A × e -kt The change is given by A, where A is the initial flow rate of the template agent solution in mL / min, and t is obtained by normalizing the coprecipitation reaction time, where 0≤t≤1 and 1.5≤k≤3.0.

[0023] (2) Place the templated precursor obtained in step (1) in the template etching solution to obtain the matrix precursor;

[0024] (3) Mix the matrix precursor obtained in step (2) with the first lithium source, and sinter to obtain the matrix;

[0025] (4) The matrix obtained in step (3) is immersed in a coating solution including a boron source, a phosphorus source and a second lithium source, and the solid and liquid are separated. The solid is subjected to microwave pulse treatment and heat treatment in sequence to obtain the high nickel cathode material.

[0026] This invention employs a strategy of programmatically controlling the flow rate of the template agent solution. Using a precision metering pump, the real-time flow rate of the template agent solution varies according to a preset mathematical model. This allows for controllable, in-situ variation of the template agent content at different growth stages of the precursor during the co-precipitation reaction, following the preset mathematical model. Finally, etching yields a matrix precursor with a gradient pore structure that varies according to the preset mathematical model. The programmatic control of the template agent solution flow rate and the introduction of the mathematical model effectively improve the uniformity of the porosity of the prepared matrix, laying the foundation for industrial-scale production.

[0027] By controlling the flow rate of the template agent solution according to V(t)=A×e -ktThe template solution is introduced in a predictable manner, initially rapidly decreasing in flow rate followed by a slow, exponential decay. During the nucleation phase of the precursor, a high-flow-rate template solution forms crystal nuclei with a dense template. As the crystal nuclei continue to grow, the template density in the precursor decreases exponentially with the flow rate of the template solution, eventually resulting in a sparse template on the surface. In subsequent etching, the dense template is etched to form a highly porous crystal nucleus, providing a rapid ion transport channel and effectively buffering volumetric strain. The exponentially decaying template constructs a porous structure with the same exponential decay trend, while the sparse template on the surface is etched to form a low-porosity, dense structure, maintaining high tap density and improving the mechanical strength of the substrate. Simultaneously, the external dense region provides an ideal substrate for the uniform construction of the ultrathin glassy lithium boron phosphorus oxide coating.

[0028] This application combines microwave pulse post-processing technology, under the instantaneous selective heating of pulsed microwaves, to rapidly react boron and phosphorus sources pre-impregnated on the substrate surface with a second lithium source, generating a uniform glassy coating layer in situ. Microwave pulse post-processing not only enables the in-situ construction of an ultrathin, uniform, and highly ionicly conductive glassy lithium boron phosphorus oxide coating layer, effectively eliminating interfacial side reactions, but also minimizes ion transport impedance and thermal damage.

[0029] In some embodiments of this application, the initial flow rate A of the template agent solution in step (1) is obtained in the following manner:

[0030] The template agent solution is delivered at an arbitrary constant flow rate A x The matrix precursor was prepared according to steps (1) to (2), and the D50 particle size D of the matrix precursor was tested. x With average porosity ε x The system constant C=A is obtained. x / (ε x ×D x ), where A x The unit is mL / min, D x The unit for C is μm, and the unit for C is mL·μm. -1 ·min -1 The initial flow rate of the template agent solution is A = C × ε0 × D, where ε0 is the target average porosity of the matrix precursor, D is the target D50 particle size of the templated precursor, and the unit of D is μm.

[0031] In some embodiments of this application, the template agent in the template agent solution of step (1) includes tetraethyl orthosilicate and / or tetramethyl orthosilicate.

[0032] In some embodiments of this application, the solvent of the template agent solution in step (1) includes any one or a combination of at least two of methanol, ethanol, isopropanol or n-butanol.

[0033] In some embodiments of this application, the concentration of the template agent in the template agent solution in step (1) is 0.5 mol / L to 1.5 mol / L.

[0034] In some embodiments of this application, the template etching agent in the template etching solution of step (2) includes sodium hydroxide and / or potassium hydroxide.

[0035] In some embodiments of this application, the concentration of the template etchant in the template etching solution in step (2) is 1 mol / L to 3 mol / L.

[0036] In some embodiments of this application, the boron source in the coating solution of step (4) includes boric acid.

[0037] In some embodiments of this application, the phosphorus source in the coating solution in step (4) includes any one or a combination of at least two of phosphoric acid, hydrogen phosphate, ammonium dihydrogen phosphate, or ammonium phosphate.

[0038] In some embodiments of this application, the second lithium source in the coating solution of step (4) includes any one or a combination of at least two of lithium hydroxide, lithium nitrate, lithium chloride or lithium acetate.

[0039] In some embodiments of this application, based on the total molar amounts of B, P and Li in the boron source, phosphorus source and the second lithium source, the molar ratio of B, P and Li in the coating solution described in step (4) is 1:(0.05~0.2):(0.8~1.2).

[0040] In some embodiments of this application, the solvent of the coating solution in step (4) includes a mixture of ethanol and water.

[0041] In some embodiments of this application, the sintering in step (3) is carried out in an oxygen-containing atmosphere.

[0042] In some embodiments of this application, the sintering temperature in step (3) is 650°C to 850°C.

[0043] In some embodiments of this application, the sintering time in step (3) is 10h~15h.

[0044] In some embodiments of this application, the microwave pulse processing in step (4) is performed under an inert atmosphere.

[0045] In some embodiments of this application, the power of the microwave pulse processing in step (4) is 2.5kW to 3.5kW.

[0046] In some embodiments of this application, the single pulse duration of the microwave pulse processing in step (4) is 0.3s to 0.8s.

[0047] In some embodiments of this application, the interval between two adjacent microwave pulses in step (4) is 0.5s to 1.5s.

[0048] In some embodiments of this application, the heat treatment in step (4) is performed under an inert atmosphere.

[0049] In some embodiments of this application, the temperature of the heat treatment in step (4) is 250°C to 400°C.

[0050] In some embodiments of this application, the heat treatment time in step (4) is 1h to 3h.

[0051] Thirdly, this application provides a positive electrode sheet, the positive electrode sheet comprising the high-nickel positive electrode material as described in the first aspect, or the positive electrode sheet comprising the high-nickel positive electrode material prepared by the preparation method described in the second aspect.

[0052] Fourthly, this application provides a lithium-ion battery, the lithium-ion battery comprising a high-nickel cathode material as described in the first aspect, or the lithium-ion battery comprising a high-nickel cathode material prepared by the preparation method described in the second aspect, or the lithium-ion battery comprising a cathode sheet as described in the third aspect.

[0053] Compared with the prior art, the present invention has the following beneficial effects:

[0054] (1) This application constructs a three-dimensional interconnected porous structure with an exponentially decreasing core-to-surface ratio within the matrix of a high-nickel cathode material, and constructs an ultrathin glassy lithium boron phosphorus oxide coating layer on the matrix surface to work in synergy with it, while maintaining a compaction density ≥3.5 g / cm³. 3 At the same time, it achieves a high discharge specific capacity of ≥240mAh / g and a long cycle life of ≥95% retention rate for 100 cycles, while reducing cycle gas production by more than 65%, achieving high safety and solving the problem of mutual constraints between rate performance, energy density, cycle performance and safety performance of high-nickel cathode materials.

[0055] (2) The present invention adopts a programmatic control strategy for the inflow rate of template agent solution, and the inflow flow control based on mathematical model realizes the quantification, predictability and reproducibility of the process, and the product consistency is good.

[0056] (3) This application uses microwave pulse post-processing technology to construct an ultra-thin, uniform and highly ionic conductive glassy lithium boron phosphorus oxide coating layer on the substrate surface in situ, which effectively eliminates interfacial side reactions while minimizing ion transport impedance and thermal damage. Attached Figure Description

[0057] Figure 1This is the curve showing the change in the flow rate of the template agent solution as a function of normalization time in Example 1.

[0058] Figure 2 This is a SEM image of the surface of the matrix precursor prepared in Example 1.

[0059] Figure 3 This is a SEM image of the cross-section of the matrix precursor prepared in Example 1.

[0060] Figure 4 This is a SEM image of the surface of the high-nickel cathode material prepared in Example 1.

[0061] Figure 5 This is a SEM image of the cross-section of the high-nickel cathode material prepared in Example 1. Detailed Implementation

[0062] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.

[0063] The scope of this invention can be defined by lower and upper limits. The selected lower and upper limits define the boundaries of a specific range. The range defined in this way can be defined by the inclusion or exclusion of endpoints. Any endpoint can be independently selected for inclusion or exclusion, and all lower and upper limits can be arbitrarily combined to form new ranges. That is, any lower limit can be combined with any upper limit to form an effective range. For example, if the ranges of 60~120 and 80~110 are listed for specific parameters, it should be understood that the ranges of 60~110 and 80~120 also fall within the scope of this invention. In addition, if the minimum range values ​​1 and 2 are listed, and the maximum range values ​​3, 4 and 5 are also listed, then all ranges of 1~3, 1~4, 1~5, 2~3, 2~4 and 2~5 fall within the scope of this invention. In this invention, the numerical range "a~b" represents a shortened representation of any combination of real numbers between a and b, where a and b are both real numbers. For example, the numerical range "0~5" means that all real numbers between 0 and 5 have been fully listed in this document, and "0~5" is only a shortened representation of this set of numerical combinations. When a parameter is expressed as an integer ≥2, it is equivalent to listing positive integers that meet the requirements, such as 2, 3, 4, 5, 6, 7, 8, 9, 10, etc. When a parameter is expressed as an integer selected from "2~10", it is equivalent to listing any integer among 2, 3, 4, 5, 6, 7, 8, 9, and 10.

[0064] In this invention, "a combination of at least two" refers to a quantity greater than or equal to 2 unless otherwise specified. For example, "any one or a combination of at least two" means that any one of the listed items can be selected, or a combination of at least two of the listed items formed in a manner that does not conflict and enables the implementation of this invention. In this invention, unless otherwise specified, the features or solutions corresponding to "and / or" cover any one of two or more related listed items, as well as any and all combinations of the related listed items. The arbitrary and all combinations include any two related listed items, any more related listed items, or a combination of all related listed items. For example, "A and / or B" means a set consisting of A, B, and combinations of A and B, where "containing A and / or B" can be understood, depending on the context of the statement, as containing A, containing B, or simultaneously containing both A and B. In this invention, "optional" means that the corresponding feature, component, step or solution is not necessary, that is, it is selected from either "with" or "without". If there are multiple "optional" limitations in a technical solution, unless otherwise specified and there is no technical conflict or mutual constraint, each "optional" limitation is independent and does not affect the others.

[0065] In this invention, technical features or solutions described using open-ended terms such as "comprising" or "including" do not exclude additional non-conflicting elements beyond the listed elements unless otherwise specified. They are considered to disclose both closed-ended features or solutions consisting solely of the listed elements and open-ended features or solutions that may include additional non-conflicting elements beyond the listed elements. For example, if A includes a1, a2, and a3, unless otherwise specified, this means that A can consist only of a1, a2, and a3, or it can include other non-conflicting elements based on a1, a2, and a3. This corresponds to the disclosure of technical solutions such as "A consists of a1, a2, and a3," "A is selected from a1, a2, and a3," and "A not only includes a1, a2, and a3, but may also include other non-conflicting elements." All embodiments and optional embodiments of this invention, unless otherwise specified and without technical conflict, can be combined to form new technical solutions, and such combinations fall within the scope of this invention. The term "embodiment" as used in this invention means that a specific feature, structure, or characteristic described in connection with an embodiment may be included in at least one embodiment or implementation of the invention. The appearance of this phrase in various locations throughout the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment mutually exclusive with other embodiments. Those skilled in the art will understand, explicitly and implicitly, that the embodiments described in this invention can be combined with other embodiments that do not conflict with the technology. The ordinal numbers "first," "second," "third," and "fourth," etc., used in the expressions "first aspect," "second aspect," "third aspect," and "fourth aspect" in this invention are for descriptive purposes only and should not be construed as indicating or implying relative importance or quantity, nor should they be construed as implicitly specifying the importance or quantity of the indicated technical features. They serve only as a non-exhaustive enumeration and do not constitute a closed limitation on quantity.

[0066] In this invention, the order in which the steps are written in the methods described in each embodiment does not imply a strict execution order. The actual execution order of each step should be determined based on its function and possible internal logic. Unless otherwise specified, all steps of this invention can be executed in the order they are written, or in any order without technical conflict. For example, if the method includes steps (a) and (b), it means that the method may include steps (a) and (b) executed sequentially, or it may include steps (b) and (a) executed sequentially. If the method also includes step (c), then step (c) can be added to the method in any order without conflict, including but not limited to the execution order of steps (a), (b), and (c), steps (a), (c), and (b), steps (c), (a), and (b), etc.

[0067] In one specific embodiment, the present invention provides a high-nickel cathode material, the high-nickel cathode material comprising a substrate and a coating layer; the chemical formula of the substrate includes LiNi. x Coy M z O2, where M includes Mn and / or Al, x ≥ 0.6, for example, it can be 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9, 0.92, 0.94 or 0.96; 0 ≤ y ≤ 0.4, for example, it can be 0, 0.05, 0.1, 0.15, 0.2, 0.25, 0.3, 0.35 or 0.4, z = 1 - xy; the average porosity in the matrix within the range of 0 to 1 / 20R from the core is φ0, and the porosity within the range of 1 / 20R to R from the core follows an exponential gradient distribution, satisfying: φ(r) = φ0 × e -kr r is obtained by normalizing the radius R of the substrate, 1 / 20 < r ≤ 1, for example, it can be 0.06, 0.1, 0.2, 0.4, 0.6, 0.8 or 1; 1.5 ≤ k ≤ 3.0, for example, it can be 1.5, 1.8, 2.0, 2.2, 2.5, 2.8 or 3.0; the material of the coating layer includes glassy lithium boron phosphorus oxide.

[0068] This application identifies the comprehensive influence of internal porosity of high-nickel cathode material particles on rate performance and compaction density, and constructs a three-dimensional through-pore structure within the high-nickel cathode material matrix, with the porosity decreasing exponentially from the core to the surface: the average porosity of the crystal nuclei within the range of 0 to 1 / 20R from the core is φ0, and as the crystal nuclei continue to grow, the porosity follows the formula φ(r) = φ0 × e. -kr The transition is continuous, where r is obtained by normalizing the radius R of the matrix, 1 / 20 < r ≤ 1, and k is the attenuation constant, which uniquely determines the gradient steepness of the pore formation. The larger the value of k, the faster the pores attenuate from the inside to the outside, and the stronger the contrast between "sparse inside and dense outside".

[0069] This application effectively avoids stress concentration by selecting the k value to control the steepness of porosity change. The internal loose region provides a fast ion transport channel and effectively buffers volumetric strain, while the external dense region effectively maintains high tap density, giving the particles high compressive strength. At the same time, it provides an ideal substrate for the uniform construction of ultrathin glassy lithium boron phosphorus oxide coating. The uniform and dense glassy lithium boron phosphorus oxide coating has high lithium-ion conductivity and can protect the porous structure from electrolyte corrosion and effectively suppress side reaction gas production.

[0070] This application designs the internal pore structure of the high-nickel cathode material matrix and constructs an ultra-thin glassy lithium boron phosphorus oxide coating layer on the matrix surface to work synergistically with it. This ensures that the high-nickel cathode material has high tap density and compaction density, while effectively improving the ion transport capacity and structural stability of the high-nickel cathode material, protecting the matrix from electrolyte corrosion, reducing side reaction gas production, and achieving simultaneous improvement in rate performance and cycle performance.

[0071] In some embodiments, the average porosity of the matrix in the range of 0 to 1 / 20R from the core is 40% to 50%, for example, it can be 40%, 42%, 44%, 46%, 48% or 50%, and the average porosity in the range of 19 / 20R to R from the core is 1% to 10%, for example, it can be 1%, 2%, 4%, 6%, 8% or 10%.

[0072] In some embodiments, the average porosity of the matrix is ​​15% to 25%, for example, it can be 15%, 18%, 20%, 21%, 23% or 25%.

[0073] In some embodiments, the thickness of the coating layer is 2nm to 20nm, for example, it can be 2nm, 5nm, 10nm, 12nm, 14nm, 16nm, 18nm or 20nm.

[0074] In some embodiments of this application, the molar ratio of B, P, and Li in the glassy lithium boron phosphorus oxide is 1:(0.05~0.2):(0.8~1.2), for example, it can be 0.8:0.05:0.8, 0.9:0.08:0.88, 1:0.1:1, 1:0.15:1.1, or 1:0.2:1.2.

[0075] In some embodiments, the tap density of the high-nickel cathode material is 2.3 g / cm³. 3 The above, for example, could be 2.3 g / cm³. 3 2.35g / cm 3 2.4g / cm 3 2.45g / cm 3 2.5g / cm 3 2.55g / cm 3 2.6g / cm 3 2.65g / cm 3 2.7g / cm 3 2.75g / cm 3 2.8g / cm 3 2.85g / cm 3 2.9g / cm 3 2.95g / cm 3 Or 3g / cm 3 .

[0076] In some embodiments, the D50 particle size of the high-nickel cathode material is 8μm to 15μm, for example, it can be 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm or 15μm.

[0077] In some embodiments, the matrix of the high-nickel cathode material further includes doping elements, which include any one or a combination of at least two of Al, Mg, Zr, Ti, Nb, Mo, W, B, or F.

[0078] In another specific embodiment, this application provides a method for preparing a high-nickel cathode material as described in the foregoing specific embodiment, the method comprising:

[0079] (1) A mixed metal salt solution of Ni salt, Co salt and M salt, a precipitant solution, a complexing agent solution and a template agent solution are introduced into the reactor in parallel to coprecipitate the precursor to obtain a templated precursor.

[0080] During the co-precipitation process, the flow rates of the mixed metal salt solution, precipitant solution, and complexing agent solution are kept constant, while the flow rate of the template agent solution is determined according to V(t) = A × e -kt The change is given by A, where A is the initial flow rate of the template agent solution in mL / min, and t is obtained by normalizing the coprecipitation reaction time. 0 ≤ t ≤ 1, for example, it can be 0, 0.2, 0.4, 0.6, 0.8 or 1; 1.5 ≤ k ≤ 3.0, for example, it can be 1.5, 1.8, 2.0, 2.2, 2.5, 2.8 or 3.0.

[0081] (2) Place the templated precursor obtained in step (1) in the template etching solution to obtain the matrix precursor;

[0082] (3) Mix the matrix precursor obtained in step (2) with the first lithium source, and sinter to obtain the matrix;

[0083] (4) The matrix obtained in step (3) is immersed in a coating solution including a boron source, a phosphorus source and a second lithium source, and the solid and liquid are separated. The solid is subjected to microwave pulse treatment and heat treatment in sequence to obtain the high nickel cathode material.

[0084] This invention employs a strategy of programmatically controlling the flow rate of the template agent solution. Using a precision metering pump, the real-time flow rate of the template agent solution varies according to a preset mathematical model. This allows for controllable, in-situ variation of the template agent content at different growth stages of the precursor during the co-precipitation reaction, following the preset mathematical model. Finally, etching yields a matrix precursor with a gradient pore structure that varies according to the preset mathematical model. The programmatic control of the template agent solution flow rate and the introduction of the mathematical model effectively improve the uniformity of the porosity of the prepared matrix, laying the foundation for industrial-scale production.

[0085] By controlling the flow rate of the template agent solution according to V(t)=A×e -ktThe template solution is introduced in a predictable manner, initially rapidly decreasing in flow rate followed by a slowing, exponential decay. During the nucleation phase of the precursor, the high flow rate of the template solution quickly forms crystal nuclei with dense templates. As the crystal nuclei continue to grow, the template density in the precursor decreases exponentially with the flow rate of the template solution, eventually resulting in a sparse template on the surface. In subsequent etching, the dense template is etched to form highly porous crystal nuclei, providing rapid ion transport channels and effectively buffering volumetric strain. The exponentially decaying template constructs a porous structure with the same exponential decay trend, while the sparse template on the surface is etched to form a low-porosity, dense structure, maintaining high tap density and improving the mechanical strength of the substrate. Simultaneously, the external dense region provides an ideal substrate for the uniform construction of the ultrathin glassy lithium boron phosphorus oxide coating.

[0086] This application combines microwave pulse post-processing technology, under the instantaneous selective heating of pulsed microwaves, to rapidly react boron and phosphorus sources pre-impregnated on the substrate surface with a second lithium source, generating a uniform glassy coating layer in situ. Microwave pulse post-processing not only enables the in-situ construction of an ultrathin, uniform, and highly ionicly conductive glassy lithium boron phosphorus oxide coating layer, effectively eliminating interfacial side reactions, but also minimizes ion transport impedance and thermal damage.

[0087] In some embodiments, the initial flow rate A of the template agent solution in step (1) is obtained in the following manner:

[0088] The template agent solution is delivered at an arbitrary constant flow rate A x The matrix precursor was prepared according to steps (1) to (2), and the D50 particle size D of the matrix precursor was tested. x With average porosity ε x The system constant C=A is obtained. x / (ε x ×D x ), where A x The unit is mL / min, D x The unit for C is μm, and the unit for C is mL·μm. -1 ·min -1 The initial flow rate of the template agent solution is A = C × ε0 × D, where ε0 is the target average porosity of the matrix precursor, D is the target D50 particle size of the templated precursor, and the unit of D is μm.

[0089] This application regulates the porosity of the matrix by first calibrating the system constant and then calculating the initial flow rate based on the design target. The system constant fluctuates only with changes in the equipment. Under specific reaction apparatus and fixed process conditions, only one calibration is required. By setting the target average porosity and target D50 particle size of the material, a unique and correct initial flow rate can be directly and quantitatively calculated, achieving precise and controllable production. In some embodiments, the total concentration of Ni, Co, and M in the mixed metal salt solution described in step (1) is 1 mol / L to 4 mol / L, for example, it can be 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, 3 mol / L, 3.5 mol / L, or 4 mol / L.

[0090] In some embodiments, the Ni salt in the mixed metal salt solution of step (1) includes any one or a combination of at least two of nickel nitrate, nickel chloride, nickel sulfate, or nickel acetate.

[0091] In some embodiments, the Co salt in the mixed metal salt solution of step (1) includes any one or a combination of at least two of cobalt nitrate, cobalt chloride, cobalt sulfate, or cobalt acetate.

[0092] In some embodiments, in the mixed metal salt solution of step (1), the M salt includes Mn salt and / or Al salt, wherein the Mn salt includes any one or a combination of at least two of manganese nitrate, manganese chloride, manganese sulfate or manganese acetate; and the Al salt includes any one or a combination of at least two of aluminum nitrate, aluminum chloride or aluminum sulfate.

[0093] In some embodiments, the concentration of the precipitant in the precipitant solution in step (1) is 2 mol / L to 8 mol / L, for example, it can be 2 mol / L, 3 mol / L, 4 mol / L, 5 mol / L, 6 mol / L, 7 mol / L or 8 mol / L.

[0094] In some embodiments, the precipitant solution in step (1) includes any one or a combination of at least two of sodium hydroxide, potassium hydroxide, sodium carbonate, sodium bicarbonate, or ammonia.

[0095] In some embodiments, the concentration of the complexing agent in the complexing agent solution in step (1) is 0.1 mol / L to 2 mol / L, for example, it can be 0.1 mol / L, 0.5 mol / L, 0.8 mol / L, 1 mol / L, 1.3 mol / L, 1.5 mol / L, 1.8 mol / L or 2 mol / L.

[0096] In some embodiments, the complexing agent in the complexing agent solution of step (1) includes any one or a combination of at least two of ammonia, citric acid, disodium ethylenediaminetetraacetate, or oxalic acid.

[0097] In some embodiments, the reactor in step (1) includes a base liquid, which includes a sodium hydroxide solution, the volume of which is 1 / 3 to 1 / 2 of the reactor volume, and the pH of which is 10 to 12.

[0098] In some embodiments, the template agent in the template agent solution of step (1) includes tetraethyl orthosilicate and / or tetramethyl orthosilicate.

[0099] In some embodiments, the solvent of the template agent solution in step (1) includes any one or a combination of at least two of methanol, ethanol, isopropanol or n-butanol.

[0100] In some embodiments, the concentration of the template agent in the template agent solution in step (1) is 0.5 mol / L to 1.5 mol / L, for example, it can be 0.5 mol / L, 0.7 mol / L, 0.9 mol / L, 1 mol / L, 1.1 mol / L, 1.3 mol / L or 1.5 mol / L.

[0101] In some embodiments, the template etching solution in step (2) includes sodium hydroxide and / or potassium hydroxide as the template etchant.

[0102] In some embodiments, the concentration of the template etchant in the template etching solution in step (2) is 1 mol / L to 3 mol / L, for example, it can be 1 mol / L, 1.2 mol / L, 1.5 mol / L, 1.8 mol / L, 2 mol / L, 2.2 mol / L, 2.5 mol / L, 2.8 mol / L or 3 mol / L.

[0103] In some embodiments, the pH of the coprecipitation reaction is 8 to 12, for example, it can be 8, 9, 10, 11 or 12.

[0104] In some embodiments, the temperature of the coprecipitation reaction is 40°C to 80°C, for example, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C or 80°C.

[0105] In some embodiments, the rotation speed of the coprecipitation reaction is 300 rpm to 600 rpm, for example, 300 rpm, 350 rpm, 400 rpm, 450 rpm, 500 rpm, 550 rpm or 600 rpm.

[0106] In some embodiments, the reactor includes a thickener.

[0107] This application uses a reactor equipped with a thickener for coprecipitation reaction. The thickener can retain all the solid particles obtained from the coprecipitation reaction in the reactor to ensure precise control of the material in the reactor, so that the prepared templated precursor has uniform particle size and good consistency.

[0108] In some embodiments, the boron source in the coating solution of step (4) includes boric acid.

[0109] In some embodiments, the phosphorus source in the coating solution in step (4) includes any one or a combination of at least two of phosphoric acid, ammonium hydrogen phosphate, ammonium dihydrogen phosphate, or ammonium phosphate.

[0110] In some embodiments, the second lithium source in the coating solution of step (4) includes any one or a combination of at least two of lithium hydroxide, lithium nitrate, lithium chloride, or lithium acetate.

[0111] In some embodiments, based on the total molar amounts of B, P and Li in the boron source, phosphorus source and the second lithium source, the molar ratio of B, P and Li in the coating solution described in step (4) is 1:(0.05~0.2):(0.8~1.2), for example, it can be 0.8:0.05:0.8, 0.9:0.08:0.88, 1:0.1:1, 1.1:0.15:1.1 or 1.2:0.2:1.2.

[0112] In some embodiments, the solvent of the coating solution in step (4) includes a mixture of ethanol and water.

[0113] In some embodiments, the volume ratio of ethanol to water in the solvent of the coating solution in step (4) is 1:(8~10), for example, it can be 1:8, 1:8.2, 1:8.5, 1:8.7, 1:9, 1:9.2, 1:9.5, 1:9.7 or 1:10.

[0114] In some embodiments, the sintering in step (3) is carried out in an oxygen-containing atmosphere.

[0115] In this application, the oxygen-containing atmosphere includes oxygen and / or air.

[0116] In some embodiments, the sintering temperature in step (3) is 650°C to 850°C, for example, it can be 650°C, 700°C, 750°C, 800°C or 850°C.

[0117] In some embodiments, the sintering time in step (3) is 10h to 15h, for example, it can be 10h, 11h, 12h, 13h, 14h or 15h.

[0118] In some embodiments, step (3) of the first lithium source includes any one or a combination of at least two of lithium nitrate, lithium chloride, lithium carbonate, lithium hydroxide, or lithium acetate.

[0119] In some embodiments, when the mixed matrix precursor in step (3) is mixed with the first lithium source, a dopant is also added and mixed together. The dopant includes any one or a combination of at least two of aluminum nitrate, aluminum chloride, magnesium nitrate, magnesium oxide, zirconium oxide, titanium dioxide, niobium pentoxide, ammonium molybdate, molybdenum dioxide, ammonium tungstate, tungsten dioxide, boric acid, lithium borate, or lithium fluoride.

[0120] In some embodiments, the microwave pulse processing in step (4) is performed in an inert atmosphere.

[0121] In some implementations, the power of the microwave pulse processing in step (4) is 2.5kW to 3.5kW, for example, it can be 2.5kW, 2.7kW, 2.9kW, 3kW, 3.3kW or 3.5kW.

[0122] In some implementations, the duration of a single pulse in the microwave pulse processing in step (4) is 0.3s to 0.8s, for example, it can be 0.3s, 0.4s, 0.5s, 0.6s, 0.7s or 0.8s.

[0123] In some embodiments, the interval between two adjacent microwave pulses in step (4) is 0.5s to 1.5s, for example, it can be 0.5s, 0.7s, 0.9s, 1s, 1.1s, 1.3s or 1.5s.

[0124] In some embodiments, the heat treatment in step (4) is performed under an inert atmosphere.

[0125] The inert atmosphere described in this application includes nitrogen and / or an inert gas, wherein the inert gas includes argon and / or helium.

[0126] In some embodiments, the temperature of the heat treatment in step (4) is 250°C to 400°C, for example, it can be 250°C, 300°C, 350°C or 400°C.

[0127] In some implementations, the heat treatment time in step (4) is 1h to 3h, for example, it can be 1h, 1.5h, 2h, 2.5h or 3h.

[0128] In yet another embodiment, this application provides a positive electrode sheet comprising a high-nickel positive electrode material as described in one embodiment above, or the positive electrode sheet comprising a high-nickel positive electrode material prepared by the preparation method described in another embodiment above.

[0129] In another specific embodiment, this application provides a lithium-ion battery, the lithium-ion battery comprising a high-nickel cathode material as described in one of the preceding specific embodiments, or the lithium-ion battery comprising a high-nickel cathode material prepared by the preparation method described in another of the preceding specific embodiments, or the lithium-ion battery comprising a cathode sheet as described in yet another of the preceding specific embodiments.

[0130] The numerical range described in this invention includes not only the point values ​​listed above, but also any point values ​​within the numerical ranges not listed above. Due to space limitations and for the sake of brevity, this invention will not exhaustively list all the specific point values ​​included in the range.

[0131] To clearly illustrate the technical solution of the present invention, in the specific embodiments, all high-nickel cathode materials provided in the examples and comparative examples are prepared in the same 50L reactor equipped with a thickener, so as to avoid the influence of equipment fluctuations on the material performance.

[0132] This application first calibrates the system constant C of the reactor used to confirm the initial flow rate before preparing the high-nickel cathode material in each embodiment and comparative example. The calibration method for the system constant C includes:

[0133] A mixed metal salt solution with a molar ratio of Ni, Co, and Mn of 0.94:0.05:0.01 and a total ion concentration of Ni, Co, and Mn of 2 mol / L is provided. A 4 mol / L NaOH solution is used as a precipitant solution, a 0.5 mol / L ammonia solution is used as a complexing agent solution, and a 1 mol / L tetraethyl orthosilicate ethanol solution is used as a template agent solution. A sodium hydroxide solution with a pH of 11 is added to the reactor, and the temperature is raised to 60°C to serve as the bottom liquid. The volume of the bottom liquid is half the volume of the reactor.

[0134] The above-mentioned mixed metal salt solution, precipitant solution, complexing agent solution, and template agent solution were introduced concurrently into the reactor for co-precipitation until the particle D50 size reached 10 μm, yielding the templated precursor. During the co-precipitation reaction, the pH was maintained at 11.5, the temperature at 60℃, the flow rate of the mixed metal salt solution was kept constant at 3 L / h, the initial flow rate of the precipitant solution was set to 3 L / h, the pH was tested every 0.5 h, and the pH was decreased by 0.02 per hour by adjusting the precipitant flow rate, the flow rate of the complexing agent solution was kept constant at 0.6 L / h, and the initial flow rate of the template agent solution was 45 L / min. Taking k=2, the reaction was performed according to V(t)=45×e -2t change.

[0135] The templated precursor was placed in a 2 mol / L sodium hydroxide solution to completely remove the silica template, resulting in a porous precursor. The porosity of the porous precursor was measured to be 15%, and the system constant C was calculated to be 45 / (0.15×10) = 30 (mL·μm). -1 ·min -1 ).

[0136] In all embodiments and comparative examples of this application, the calculated C=30 (mL·μm) is used. -1 ·min -1 ) is a system constant.

[0137] The above description is only for clearly illustrating the technical solution of the present invention and is not intended to further limit the present invention.

[0138] Example 1

[0139] This embodiment provides a high-nickel cathode material, comprising a substrate and a coating layer, wherein the chemical formula of the substrate is LiNi. 0.94 Co 0.05 Mn 0.01 The average porosity of O2 in the matrix is ​​45% in the range of 0 to 1 / 20R from the core, and 6% in the range of 19 / 20R to R from the core. The porosity of the matrix follows an exponential gradient distribution, satisfying φ(r) = 0.45 × e from the core to the surface. -2r The average porosity of the matrix is ​​20%; the coating material consists of a 10 nm thick glassy lithium boron phosphorus oxide, in which the molar ratio of B, P, and Li is 1:0.1:1; the tap density of the high-nickel cathode material is 2.32 g / cm³. 3 The D50 particle size is 12μm.

[0140] This embodiment also provides a method for preparing the above-mentioned high-nickel cathode material, the method comprising:

[0141] (1) Prepare a mixed metal salt solution with a molar ratio of Ni, Co and Mn of 0.94:0.05:0.01 and a total ion concentration of Ni, Co and Mn of 2 mol / L. Use a 4 mol / L NaOH solution as a precipitant solution, a 0.5 mol / L ammonia solution as a complexing agent solution, and a 1 mol / L tetraethyl orthosilicate ethanol solution as a template agent solution. Add a sodium hydroxide solution with a pH of 11.5 to the reactor and heat it to 60℃ as the bottom liquid. The volume of the bottom liquid is half the volume of the reactor.

[0142] The above-mentioned mixed metal salt solution, precipitant solution, complexing agent solution, and template agent solution were introduced concurrently into the reactor for co-precipitation until the particle D50 size reached 12 μm, yielding the templated precursor. During the co-precipitation reaction, the pH was maintained at 11.5, the temperature at 60℃, the flow rate of the mixed metal salt solution was kept constant at 3 L / h, the initial flow rate of the precipitant solution was set at 3 L / h, the pH was tested every 0.5 h, and the pH was decreased by 0.02 per hour by adjusting the precipitant flow rate. The flow rate of the complexing agent solution was kept constant at 0.6 L / h, and the flow rate of the template agent solution was calculated according to V(t) = A × e -2t The change, according to the system constant C=30(mL·μm) -1 ·min -1 The target average porosity ε0 is 20%, the target D50 particle size is 12 μm, and the calculated A = 30 × 0.2 × 12 = 72 mL / min is given. The curve showing the change in the flow rate of the template agent solution with normalized time is shown below. Figure 1 As shown;

[0143] (2) Collect the templated precursor obtained in step (1), wash it with deionized water, place it in a sodium hydroxide solution with a concentration of 2 mol / L to remove the silica template, wash it with deionized water until the filtrate is neutral, dry it, and obtain the matrix precursor.

[0144] (3) According to the ratio of the total molar amount of Li in lithium hydroxide to the total molar amount of transition metal elements in the matrix precursor of 1.05:1, the matrix precursor obtained in step (2) and lithium hydroxide are mixed and sintered at 750°C for 12 hours in an oxygen atmosphere to obtain the matrix.

[0145] (4) Based on the total molar amounts of B, P and Li in boric acid, ammonium dihydrogen phosphate and lithium hydroxide, and according to the molar ratio of B, P and Li of 1:0.1:1, boric acid, ammonium dihydrogen phosphate and lithium hydroxide are dissolved in a mixed solvent with a volume ratio of ethanol and water of 1:9 to obtain a coating solution with a total concentration of 0.38 mol / L. The matrix obtained in step (3) is immersed in the coating solution with a mass ratio of matrix to coating solution of 1:2. After immersion for 2 min, solid and liquid are separated. The obtained solid is placed in a microwave reactor under an argon atmosphere. The power of microwave pulse treatment is set to 3kW, the single pulse time is 0.5s, and the interval between two adjacent pulses is 1s. Microwave pulse treatment is performed. Finally, the temperature is raised to 300℃ in an argon atmosphere and heat-treated for 2 h to obtain a high-nickel cathode material.

[0146] The SEM image of the surface of the matrix precursor prepared in step (2) of this embodiment is shown below. Figure 2 As shown, the matrix precursor is spherical. Field emission scanning electron microscopy (FESEM) combined with focused ion beam (FIE) was used to cut the matrix precursor, and the SEM images of the cross-section are shown below. Figure 3 As shown, the matrix precursor exhibits a gradient pore structure that is "loose inside and dense outside".

[0147] The SEM image of the surface of the high-nickel cathode material prepared in step (4) of this embodiment is shown below. Figure 4 As shown, the high-nickel cathode material also exhibits a near-spherical shape. Field emission scanning electron microscopy (FESEM) combined with a focused ion beam was used to cut the high-nickel cathode material, and the SEM images of the cross-sections are shown below. Figure 5 As shown, it can be observed that the high-nickel cathode material inherits the pore structure of the matrix precursor and also has a gradient pore structure that is "loose inside and dense outside".

[0148] Example 2

[0149] This embodiment provides a high-nickel cathode material, comprising a substrate and a coating layer, wherein the chemical formula of the substrate is LiNi. 0.92 Co 0.05 Mn 0.03 The average porosity of the O2 matrix within the range of 0 to 1 / 20R from the core is 40%, and the average porosity within the range of 19 / 20R to R from the core is 2%. The porosity of the matrix exhibits an exponential gradient distribution, satisfying φ(r) = 40 × e from the core to the surface. -3r The average porosity of the matrix is ​​15%; the coating material consists of a 2nm thick glassy lithium boron phosphorus oxide, in which the molar ratio of B, P, and Li is 1:0.05:0.8; the tap density of the high-nickel cathode material is 2.35 g / cm³. 3 The D50 particle size is 8μm.

[0150] This embodiment also provides a method for preparing the above-mentioned high-nickel cathode material, the method comprising:

[0151] (1) Prepare a mixed metal salt solution with a molar ratio of Ni, Co and Mn of 0.92:0.05:0.03 and a total ion concentration of Ni, Co and Mn of 1 mol / L. Use 2 mol / L NaOH solution as precipitant solution, 0.3 mol / L ammonia solution as complexing agent solution, and 0.5 mol / L tetraethyl orthosilicate ethanol solution as template agent solution. Add sodium hydroxide solution with pH 10.5 to the reaction vessel and heat it to 60℃ as bottom liquid. The volume of bottom liquid is half the volume of the reaction vessel.

[0152] The above-mentioned mixed metal salt solution, precipitant solution, complexing agent solution and template agent solution are introduced into the reactor in parallel, and the co-precipitation reaction is carried out until the particle D50 size grows to 8 μm, thus obtaining the templated precursor.

[0153] During the coprecipitation reaction, the pH was maintained at 10.5, the temperature at 45℃, and the flow rate of the mixed metal salt solution was kept constant at 3 L / h. The initial flow rate of the precipitant solution was set to 3 L / h. The pH was tested every 0.5 h, and the pH was decreased by 0.015 per hour by adjusting the precipitant flow rate. The flow rate of the complexing agent solution was kept constant at 0.6 L / h, and the flow rate of the template agent solution was determined according to V(t) = A × e -3t The change, according to the system constant C=30(mL·μm) -1 ·min -1 Given that the target ε0 is 15% and the target D is 8 μm, calculate A = 30 × 0.15 × 8 = 36 mL / min;

[0154] (2) Collect the templated precursor obtained in step (1), wash it with deionized water, place it in a potassium hydroxide solution with a concentration of 1 mol / L to remove the silica template, wash it with deionized water until the filtrate is neutral, dry it, and obtain the matrix precursor.

[0155] (3) According to the ratio of the total molar amount of Li in lithium hydroxide to the total molar amount of transition metal elements in the matrix precursor of 1.05:1, the matrix precursor obtained in step (2) and lithium hydroxide are mixed and sintered at 650°C for 15 hours in an oxygen atmosphere to obtain the matrix.

[0156] (4) Based on the total molar amounts of B, P and Li in boric acid, ammonium dihydrogen phosphate and lithium hydroxide, and according to the molar ratio of B, P and Li of 1:0.05:0.8, boric acid, ammonium dihydrogen phosphate and lithium hydroxide are dissolved in a mixed solvent with a volume ratio of ethanol and water of 1:8 to obtain a coating solution with a total concentration of 0.38 mol / L. The matrix obtained in step (3) is immersed in the coating solution with a mass ratio of matrix to coating solution of 1:2. After immersion for 1 min, solid and liquid are separated. The obtained solid is placed in a microwave reactor under an argon atmosphere. The power of microwave pulse processing is set to 2.5 kW, the single pulse time is 0.3 s, and the interval between two adjacent pulses is 0.5 s. Microwave pulse processing is performed. Finally, the temperature is raised to 250 °C in an argon atmosphere and heat-treated for 1 h to obtain a high-nickel cathode material.

[0157] Example 3

[0158] This embodiment provides a high-nickel cathode material, comprising a substrate and a coating layer, wherein the chemical formula of the substrate is LiNi. 0.94 Co 0.05 Mn 0.01 The average porosity of the O2 matrix within the range of 0 to 1 / 20R from the core is 50%, and the average porosity within the range of 19 / 20R to R from the core is 10%. The porosity of the matrix exhibits an exponential gradient distribution, satisfying φ(r) = 50 × e from the core to the surface.-1.5r The average porosity of the matrix is ​​25%; the coating material consists of a 20 nm thick glassy lithium boron phosphorus oxide, in which the molar ratio of B, P, and Li is 1:0.2:1.2; the tap density of the high-nickel cathode material is 2.4 g / cm³. 3 The D50 particle size is 15μm.

[0159] This embodiment also provides a method for preparing the above-mentioned high-nickel cathode material, the method comprising:

[0160] (1) Prepare a mixed metal salt solution with a molar ratio of Ni, Co and Mn of 0.94:0.05:0.01 and a total ion concentration of Ni, Co and Mn of 4 mol / L. Use a 6 mol / L NaOH solution as a precipitant solution, a 2 mol / L ammonia solution as a complexing agent solution, and a 1.5 mol / L tetramethyl orthosilicate ethanol solution as a template agent solution. Add a sodium hydroxide solution with a pH of 12 to the reactor and heat it to 60℃ as the bottom liquid. The volume of the bottom liquid is half the volume of the reactor.

[0161] The above-mentioned mixed metal salt solution, precipitant solution, complexing agent solution and template agent solution are introduced into the reactor in parallel, and the co-precipitation reaction is carried out until the particle D50 size grows to 15 μm, thus obtaining the templated precursor.

[0162] During the coprecipitation reaction, the pH was maintained at 12, the temperature at 75℃, the flow rate of the mixed metal salt solution was kept constant at 3 L / h, the initial flow rate of the precipitant solution was set at 3 L / h, the pH was tested every 0.5 h, and the pH was decreased by 0.025 per hour by adjusting the precipitant flow rate. The flow rate of the complexing agent solution was kept constant at 0.6 L / h, and the flow rate of the template agent solution was determined according to V(t) = A × e -1.5t The change, according to the system constant C=30(mL·μm) -1 ·min -1 Given that the target ε0 is 25% and the target D is 15 μm, calculate A = 30 × 0.25 × 15 = 112.5 mL / min;

[0163] (2) Collect the templated precursor obtained in step (1), wash it with deionized water, place it in a sodium hydroxide solution with a concentration of 3 mol / L to remove the silica template, wash it with deionized water until the filtrate is neutral, dry it, and obtain the matrix precursor.

[0164] (3) According to the ratio of the total molar amount of Li in lithium hydroxide to the total molar amount of transition metal elements in the matrix precursor of 1.05:1, the matrix precursor obtained in step (2) and lithium hydroxide are mixed and sintered at 850°C for 10h in an oxygen atmosphere to obtain the matrix.

[0165] (4) Based on the total molar amounts of B, P and Li in boric acid, diammonium hydrogen phosphate and lithium nitrate, and according to the molar ratio of B, P and Li of 1:0.2:1.2, boric acid, diammonium hydrogen phosphate and lithium hydroxide were dissolved in a mixed solvent of ethanol and water with a volume ratio of 1:10 to obtain a coating solution with a total concentration of 0.38 mol / L. The matrix obtained in step (3) was immersed in the coating solution with a mass ratio of matrix to coating solution of 1:2. After immersion for 3 min, solid and liquid were separated. The obtained solid was placed in a microwave reactor under an argon atmosphere. The power of microwave pulse treatment was set to 3.5 kW, the single pulse time was 0.8 s, and the interval between two adjacent pulses was 1.5 s. Microwave pulse treatment was performed. Finally, the temperature was raised to 400 °C in an argon atmosphere and heat-treated for 1 h to obtain a high-nickel cathode material.

[0166] Example 4

[0167] This embodiment provides a high-nickel cathode material, which is the same as that in Example 1, except that the thickness of the glassy lithium boron phosphorus oxide coating layer is 30 nm.

[0168] This embodiment also provides a method for preparing the above-mentioned high-nickel cathode material. Except for step (4), in which the substrate is immersed in the coating solution for 4 minutes, the preparation method is the same as in Example 1.

[0169] Example 5

[0170] This embodiment provides a high-nickel cathode material, which is the same as in Example 1 except that the molar ratio of B, P and Li in the glassy lithium boron phosphorus oxide coating layer is 1:0.03:1.

[0171] This embodiment also provides a method for preparing the above-mentioned high-nickel cathode material. Except for step (4), in which boric acid, ammonium dihydrogen phosphate and lithium hydroxide are dissolved in a mixed solvent with a volume ratio of ethanol and water of 1:3 according to the molar ratio of B, P and Li of 1:0.03:1 to obtain the coating solution, the rest of the preparation method is the same as in Example 1.

[0172] Example 6

[0173] This embodiment provides a high-nickel cathode material, which is the same as in Example 1 except that the molar ratio of B, P and Li in the glassy lithium boron phosphorus oxide coating layer is 1:0.3:1.

[0174] This embodiment also provides a method for preparing the above-mentioned high-nickel cathode material. Except for step (4), in which boric acid, ammonium dihydrogen phosphate and lithium hydroxide are dissolved in a mixed solvent with a volume ratio of ethanol and water of 1:3 according to the molar ratio of B, P and Li of 1:0.3:1 to obtain the coating solution, the rest of the preparation method is the same as in Example 1.

[0175] Example 7

[0176] This embodiment provides a high-nickel cathode material, which is the same as in Example 1 except that the molar ratio of B, P and Li in the glassy lithium boron phosphorus oxide coating layer is 0.5:0.1:1.

[0177] This embodiment also provides a method for preparing the above-mentioned high-nickel cathode material. Except for step (4), in which boric acid, ammonium dihydrogen phosphate and lithium hydroxide are dissolved in a mixed solvent with a volume ratio of ethanol to water of 1:3 according to the molar ratio of B, P and Li of 0.5:0.1:1 to obtain the coating solution, the rest of the preparation method is the same as in Example 1.

[0178] Example 8

[0179] This embodiment provides a high-nickel cathode material, which is the same as in Example 1 except that the molar ratio of B, P and Li in the glassy lithium boron phosphorus oxide coating layer is 1:0.1:0.5.

[0180] This embodiment also provides a method for preparing the above-mentioned high-nickel cathode material. Except for step (4), in which boric acid, ammonium dihydrogen phosphate and lithium hydroxide are dissolved in a mixed solvent with a volume ratio of ethanol to water of 1:3 according to the molar ratio of B, P and Li of 1.5:0.1:1 to obtain the coating solution, the rest of the preparation method is the same as in Example 1.

[0181] Comparative Example 1

[0182] This comparative example provides a high-nickel cathode material, which is the same as that in Example 1 except that it does not include a glassy lithium boron phosphorus oxide coating layer.

[0183] This embodiment also provides a method for preparing the above-mentioned high-nickel cathode material. The preparation method is the same as that in Example 1 except that step (4) is not performed.

[0184] Comparative Example 2

[0185] This comparative example provides a high-nickel cathode material, which is the same as in Example 1 except that the coating material includes a mixture of lithium oxide, lithium borate and lithium phosphate, but does not include a glassy lithium boron phosphate oxide coating layer.

[0186] This embodiment also provides a method for preparing the above-mentioned high-nickel cathode material. Except for step (4), in which the matrix obtained in step (3) is mixed with boric acid, ammonium dihydrogen phosphate and lithium hydroxide in the same molar ratio by dry method and then sintered at 600°C for 6 hours under an argon atmosphere, the rest of the preparation method is the same as in Example 1.

[0187] Comparative Example 3

[0188] This comparative example provides a high-nickel cathode material, which is the same as that in Example 1 except that the pore structure of the matrix is ​​uniformly distributed and the average porosity is 20%.

[0189] This embodiment also provides a method for preparing the above-mentioned high-nickel cathode material. Except for step (1), in which the pumping speed of the template agent solution is always 30 mL / min, the preparation method is the same as in Example 1.

[0190] Comparative Example 4

[0191] This comparative example provides a high-nickel cathode material, which is the same as Example 1 except that the pore structure of the matrix changes linearly from the core to the surface and the average porosity is 26%.

[0192] This embodiment also provides a method for preparing the above-mentioned high-nickel cathode material. Except for step (1), in which the pumping speed of the template agent solution is linearly reduced from 72 mL / min to 10 mL / min, the preparation method is the same as in Example 1.

[0193] Performance testing:

[0194] (1) Preparation of button half-cell: The high-nickel cathode material provided in all the above examples and comparative examples was mixed with acetylene black and polyvinylidene fluoride at a mass ratio of 95:3:2, coated on the surface of copper foil, dried, and then rolled to a compaction density of 3.5 g / cm³. 3 The positive electrode is obtained, and the lithium sheet is used as the negative electrode to assemble a coin cell.

[0195] The charging and discharging voltage range was set to 2.5V~4.25V, the test temperature was 25℃, and the charging and discharging rate was 0.1C / 0.1C. The 0.1C charging specific capacity and 0.1C discharging specific capacity of the coin cell were tested. The initial efficiency of the coin cell was calculated as 0.1C discharging specific capacity / 0.1C charging specific capacity × 100%. The test results are shown in Table 1.

[0196] (2) Preparation of soft-pack full battery: The positive electrode obtained in step (1) is matched with the graphite negative electrode. The electrolyte is 1 mol / L LiPF6 EC / DEC (volume ratio 1:1) solution. A polyethylene separator is used to assemble the soft-pack lithium-ion battery. In the active layer of the graphite negative electrode, the mass ratio of graphite: conductive carbon black: CMC: SBR is 95:2.5:1:1.5.

[0197] The charge / discharge voltage was set to 3.0V~4.3V, the test temperature was 25℃, the charge / discharge rate was 1C / 1C, and the cycle charge / discharge was 100 times. The cycle capacity retention rate was calculated as the specific capacity of the 100th discharge cycle / the specific capacity of the 1st discharge cycle. The test results are shown in Table 1.

[0198] Before and after testing the cycle performance, the volume V0 of the battery before the first charge and discharge and the volume V after the 100th charge and discharge were tested by the water displacement method, and the gas production was calculated as V-V0. The gas production of the lithium-ion battery prepared in Comparative Example 1 was taken as 1. The gas production of all examples and the lithium-ion batteries provided in the comparative example were normalized. The gas production results after normalization are shown in Table 1.

[0199] Table 1

[0200]

[0201] Based on the test results in Table 1, and combined with the test results of Example 1 and Comparative Examples 1 to 4, this application constructs a three-dimensional interconnected porous structure with an exponentially decreasing core-to-surface ratio within the high-nickel cathode material matrix, and constructs an ultrathin glassy lithium boron phosphorus oxide coating layer on the matrix surface through microwave pulse treatment to synergize with it, while maintaining a compaction density ≥3.5 g / cm³. 3 At the same time, it achieves a high discharge specific capacity of ≥240mAh / g and a long cycle life of ≥95% retention rate for 100 cycles, while reducing cycle gas production by more than 65%, achieving high safety and solving the problem of mutual constraints between rate performance, energy density, cycle performance and safety performance of high-nickel cathode materials.

[0202] According to the test results of Examples 1 and 4, increasing the thickness of the glassy lithium boron phosphorus oxide coating layer will actually increase the resistance to ion migration on the surface of the high-nickel cathode material, resulting in a decrease in the rate performance of the high-nickel cathode material. Furthermore, surface polarization will lead to an increase in local voltage and an increased risk of electrolyte decomposition and gas generation.

[0203] According to the test results of Examples 1 and 5 to 8, if the proportion of B and P in the glassy lithium boron phosphorus oxide coating layer is too high or too low, the continuity of the synthesized coating layer will be poor, resulting in an increase in the amount of gas produced in the cycle.

[0204] The applicant declares that the above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.

Claims

1. A high-nickel cathode material, characterized in that, The high-nickel cathode material includes a matrix and a coating layer; The general chemical formula of the matrix includes LiNi x Co y M z O2, where M includes Mn and / or Al, x≥0.6, 0≤y≤0.4, z=1-xy; The average porosity of the matrix within the range of 0 to 1 / 20R from the core is φ0, and the porosity within the range of 1 / 20R to R from the core exhibits an exponential gradient distribution, satisfying: φ(r) = φ0 × e -kr r is obtained by normalizing the radius R of the matrix, where 1 / 20 < r ≤ 1, and 1.5 ≤ k ≤ 3.0; The coating material includes glassy lithium boron phosphorus oxide.

2. The high-nickel cathode material as described in claim 1, characterized in that, The average porosity of the matrix in the range of 0 to 1 / 20R from the core is 40% to 50%, the average porosity in the range of 19 / 20R to R from the core is 1% to 10%, and the average porosity of the matrix is ​​15% to 25%. And / or, the thickness of the coating layer is 2nm~20nm; And / or, in the glassy lithium boron phosphorus oxide, the molar ratio of B, P to Li is 1:(0.05~0.2):(0.8~1.2).

3. The high-nickel cathode material as described in claim 1 or 2, characterized in that, The tap density of the high-nickel cathode material is 2.3 g / cm³. 3 above; And / or, the D50 particle size of the high-nickel cathode material is 8μm~15μm.

4. A method for preparing the high-nickel cathode material as described in any one of claims 1 to 3, characterized in that, The preparation method includes: (1) A mixed metal salt solution of Ni salt, Co salt and M salt, a precipitant solution, a complexing agent solution and a template agent solution are introduced into the reactor in parallel to coprecipitate the precursor to obtain a templated precursor. During the co-precipitation process, the flow rates of the mixed metal salt solution, precipitant solution, and complexing agent solution are kept constant, while the flow rate of the template agent solution is determined according to V(t) = A × e -kt The change is given by A, where A is the initial flow rate of the template agent solution in mL / min, and t is obtained by normalizing the coprecipitation reaction time, where 0≤t≤1 and 1.5≤k≤3.

0. (2) Place the templated precursor obtained in step (1) in the template etching solution to obtain the matrix precursor; (3) Mix the matrix precursor obtained in step (2) with the first lithium source, and sinter to obtain the matrix; (4) The matrix obtained in step (3) is immersed in a coating solution including a boron source, a phosphorus source and a second lithium source, and the solid and liquid are separated. The solid is subjected to microwave pulse treatment and heat treatment in sequence to obtain the high nickel cathode material.

5. The preparation method according to claim 4, characterized in that, The initial flow rate A of the template agent solution in step (1) is obtained as follows: The template agent solution is delivered at an arbitrary constant flow rate A x The matrix precursor was prepared according to steps (1) to (2), and the D50 particle size D of the matrix precursor was tested. x With average porosity ε x The system constant C=A is obtained. x / (ε x ×D x ), where A x The unit is mL / min, D x The unit for C is μm, and the unit for C is mL·μm. -1 ·min -1 ; The initial flow rate of the template agent solution is A = C × ε0 × D, where ε0 is the target average porosity of the matrix precursor, D is the target D50 particle size of the templated precursor, and the unit of D is μm.

6. The preparation method according to claim 4 or 5, characterized in that, In the template agent solution of step (1), the template agent includes tetraethyl orthosilicate and / or tetramethyl orthosilicate; And / or, the solvent of the template agent solution in step (1) includes any one or a combination of at least two of methanol, ethanol, isopropanol or n-butanol; And / or, in the template agent solution described in step (1), the concentration of the template agent is 0.5 mol / L to 1.5 mol / L; And / or, in the template etching solution of step (2), the template etchant includes sodium hydroxide and / or potassium hydroxide; And / or, in the template etching solution described in step (2), the concentration of the template etchant is 1 mol / L to 3 mol / L.

7. The preparation method according to claim 4, characterized in that, The boron source in the coating solution described in step (4) includes boric acid; And / or, the phosphorus source in the coating solution in step (4) includes any one or a combination of at least two of phosphoric acid, ammonium hydrogen phosphate, ammonium dihydrogen phosphate, or ammonium phosphate; And / or, the second lithium source in the coating solution in step (4) includes any one or a combination of at least two of lithium hydroxide, lithium nitrate, lithium chloride or lithium acetate; And / or, based on the total molar amounts of B, P and Li in the boron source, phosphorus source and the second lithium source, respectively, the molar ratio of B, P and Li in the coating solution described in step (4) is 1:(0.05~0.2):(0.8~1.2); And / or, the solvent of the coating solution in step (4) includes a mixture of ethanol and water.

8. The preparation method according to claim 4, characterized in that, The sintering in step (3) is carried out in an oxygen-containing atmosphere, the sintering temperature is 650℃~850℃, and the sintering time is 10h~15h. And / or, the microwave pulse processing in step (4) is performed in an inert atmosphere, the power of the microwave pulse processing is 2.5kW~3.5kW, the single pulse time of the microwave pulse processing is 0.3s~0.8s, and the interval between two adjacent pulses of the microwave pulse processing is 0.5s~1.5s; And / or, the heat treatment in step (4) is carried out in an inert atmosphere, the temperature of the heat treatment is 250℃~400℃, and the time of the heat treatment is 1h~3h.

9. A positive electrode plate, characterized in that, The positive electrode sheet includes the high-nickel positive electrode material as described in any one of claims 1 to 3, or the positive electrode sheet includes the high-nickel positive electrode material prepared by the preparation method described in any one of claims 4 to 8.

10. A lithium-ion battery, characterized in that, The lithium-ion battery includes the high-nickel cathode material as described in any one of claims 1 to 3, or the lithium-ion battery includes the high-nickel cathode material prepared by the preparation method described in any one of claims 4 to 8, or the lithium-ion battery includes the cathode sheet as described in claim 9.

Citation Information

Patent Citations

  • Preparation method of high-nickel positive electrode material with low residual alkali, high compaction and uniform coating layer

    CN112194200A

  • High-temperature single-crystal high-nickel positive electrode material as well as preparation method and application thereof

    CN117361645A

  • High-nickel positive electrode material and preparation method thereof

    CN121839601A